Acceptability of compulsory powers in the community: the ethical considerations of mental health service users on Supervised Discharge and Guardianship. Issue 8 (2nd August 2005) - Canvin, K; Bartlett, A; Pinfold, V
Abstract : Objectives: To explore mental health service users' views of existing and proposed compulsory powers. Design: A qualitative study employing in-depth interviews. Participants were asked to respond to hypothetical questions regarding the application of compulsory powers under the Mental Health Act 1983 for people other than themselves. Setting: Community setting in Southeast England. Participants: Mental health service users subject to Supervised Discharge/Guardianship. Results: Participants considered that the use of compulsory powers was justified if there were some ultimate benefit, and if there was evidence of mental health problems, dangerousness, or a lack of insight. However, participants rejected intrusions into their autonomy and privacy. Conclusions: This paper's participants indicated that the proposed CTO may be unacceptable because it would threaten service users' autonomy. Service users' acceptance of proposed changes is conditional and they emphasised the importance of consent; there is no suggestion that consent will be required for the CTO. The findings also have implications for the exploration of mental health service users' views and how they might contribute to policy, service planning, and research.